Let's talk about 'One fungus One name'. Changes in the fungal taxonomy - Kövics, György (Acta Agraria Debreceniensis, 2015)
Mycologists have recorded a few hundred thousand Latin names for fungi and these are thought to refer to 70 000 or so separate species. The use of molecular techniques in fungal taxonomy and systematics in the last 25 years has provided massive amounts of information to clarify phylogenetic relationships, encouraged grant support, and complicated the jobs of classically-trained mycologists. Taxonomists have a reputation for being traditionalists, but the community has recently embraced the modernization of the nomenclatural rules by discarding the requirement for Latin descriptions, endorsing electronic publication, and ending the dual system of nomenclature, viz. teleomorph and anamorph names, which used parallel for the sexual and asexual phases of pleomorphic species. A group of taxonomists accepted ’The Amsterdam Declaration on Fungal Nomenclature’ and its basic principle the ’One fungus – one name’ has been incorporated in the Code of Nomenclature (’Melbourne Code’) in 2011. The next, and more difficult step will be to develop community standards for sequence-based classification. As the’One fungus – One name’ theory is a brand-new issue for the Hungarian plant doctors and practical specialists, it seems reasonable to review this to promote conversations between generations in Hungarian language.